1992
DOI: 10.1099/00222615-36-5-341
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblotting patterns with Mycoplasma pneumoniae of serum specimens from infected and non-infected subjects

Abstract: Summary. Two hundred and ninety-four serum specimens from 248 subjects, whose complement fixation (CF) titres to Mycoplasma pneumoniae were known, were further investigated by IgG immunoblotting. After analysis of M . pneumoniae proteins by SDS-PAGE, nine polypeptides (p) with mol. wts of 180-43 Kda were selected for immunoblotting studies. Antibodies to M. pneumoniae measured by immunoblotting appeared progressively with age; most subjects more than 19 years old gave positive results. For most of the polypept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…As in other countries [16,17], the main exposure to M. pneumoniae in the Israeli population occurs during school age, resulting in at least 80% of adults having antibodies (Fig. 1).…”
Section: Agreement Of Performance Among Different Tests According Tomentioning
confidence: 67%
See 1 more Smart Citation
“…As in other countries [16,17], the main exposure to M. pneumoniae in the Israeli population occurs during school age, resulting in at least 80% of adults having antibodies (Fig. 1).…”
Section: Agreement Of Performance Among Different Tests According Tomentioning
confidence: 67%
“…With the LISA IgG assay there was also a significant association between blood group B and positive or equivocal sera (63.4% of group B sera vs. 38.0% of other groups; p < 0.003). This association was also significant for unequivocally positive sera (26.8% of B group sera vs. 16.1% of other groups; p < 0.029). While this suggested that blood group B might produce some false-positive reactions with this kit, another explanation might be the cutoff calculation applied in this test, since the same association was not observed with the Immuno-Well IgG assay, which uses the same plates and reagents.…”
mentioning
confidence: 78%
“…IgG seroconversion in M. pneumoniae infected patients is estimated to occur from 3 to 8 weeks following infection. EIAs are more sensitive than both the CF and MAG tests ( Moule et al, 1987 ; Aubert et al, 1992 ; Nir-Paz et al, 2006 ) for detecting acute infection. Most EIAs implement a 96 well-microtiter plate.…”
Section: Diagnosismentioning
confidence: 97%
“…They determined that this PA test was not as specific for detection of IgM as the other tests. Aubert et al (14) felt that PA tests performed about as well as EIAs and IFAs, but Matas et al (286) reported the Meridian ImmunoCard EIA was able to detect lower levels of IgM antibodies than either the Serodia Myco II kit or CF tests. Karppelin et al (219) evaluated the Serofast (International Microbio, Toulon, France) and found it to be less sensitive than CF and EIA.…”
Section: Serologymentioning
confidence: 99%